INCREASING STUDENTS’ ENGAGEMENT IN LISTENING THROUGH STRATEGY-BASED INSTRUCTION - SUYONO SUYONO (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2015)
Strategy-based instruction is believed to able to improve students’ involvement in learning, including learning listening. Unfortunately, the lack concept of the instruction and the less training that the students have causes them still struggling in learning listening. This research report is aimed at investigating the effectiveness of using strategy-based instruction in term of students’ involvement and students’ comprehension in listening. This is a classroom action research of which the researcher and the teacher worked collaborately in implementing the strategy-based instruction. The research was done in two cycles of which each cycle was realized in three meetings. The data were collected using questionnaire and test. The finding suggests that the strategy-based instruction improve students’ learning in term of involvement and comprehension. The involvement in learning listening raised in all aspects of strategies which include cognitive, metacognitive and socio-affective strategies which reaches 30,3%. The improvement in term of involvement also affects the improvement in students’ comprehension from the average of 47 in the beginning of the study to 73 or 53% at the end of the.Key words: Students engagement, learning strategy, strategy based instruction